Біоадаптивне управління в комплексному лікуванні психоемоційних розладів у хворих на хронічну ішемію мозку - Демченко, Аліна Вікторівна; Demchenko, A. V. (My University, 2016)
Мета — оцінити клінічну ефективність впливу біоадаптивного управління як складової комплексного лікування на психоемоційний стан та когнітивні функції хворих на хронічну ішемію мозку (ХІМ). Матеріали і методи. Обстежено 55 хворих на ХІМ з використанням клініко-нейропсихологічних та інструментальних досліджень. Залежно від схеми лікування пацієнтів розподілено на дві групи: основну (п = 30) та контрольну (п = 25). В комплексному лікуванні хворих основної групи на тлі традиційної терапії використовували біоадаптивне управління у вигляді поєднаних курсів а-стимулювального і температурно-міографічного тренінгів на основі біологічного зворотного зв'язку (БЗЗ). Результати. Після комплексного лікування хворих на ХІМ із застосуванням БЗЗ-тренінгів вірогідно зменшилася кількість скарг на головний біль (р = 0,0002), запаморочення (р = 0,001), похитування при ходьбі (р = 0,003), порушення сну (р = 0,094), дратівливість (р = 0,027), тривожність (0,013), зросла концентрація уваги та поліпшилася пам'ять (р = 0,001) порівняно з групою контролю, в якій вірогідно змінилася вираженість скарг на головний біль, запаморочення та похитування при ходьбі. У пацієнтів основної групи статистично значущо знизився рівень реактивної (р < 0,01) та особистісної (р < 0,001) тривожності за тестом Спілбергера—Ханіна. Депресивні симптоми регресували у 40 % пацієнтів основної групи та 12 % — контрольної. Після БЗЗ-тренінгів у хворих на ХІМ установлено вірогідне скорочення латентного періоду когнітивного викликаного потенціалу Р300 за Фрідманом (р) ^3 = 0,003, F4 = 0,015, Fz = 0,039, С3 = 0,008, С4 = 0,016, Cz = 0,011, Р3 = 0,010, Р4 = 0,017, Pz = 0,007) та вірогідне підвищення а-активності в правій лобній і тім'яно-потилично-скроневій ділянках. Objective — to estimate clinical efficiency of bioadaptive control influence on psycho-emotional state and cognitive functions of patients with chronical cerebral ischemia (CCI) in complex treatment. Methods and subjects. 55 patients with CCI were evaluated for clinical and neuropsychological, instrumental and statistical methods of investigation. Patients were divided into 2 groups depending on the scheme of treatment: basic (n = 30) and control (n = 25). The complex treatment of patients from the basic group involved the traditional therapy combined with bioadaptive control in the form of united courses of alpha-stimulating and temperature-myograhic trainings based on biological feedback (BFB). Results. After complex treatment of patients with CCI using BFB trainings the following data were achieved: decreased the number of complaints for headache (p = 0.0002), dizziness (p = 0.001), staggering while walking (p = 0.003), sleep disturbance (p = 0.094), irritability (p = 0.027), anxiety (p = 0.013), the concentration of attention and memory (p = 0.001) improved in comparison with control group, where the complaints for headache, dizziness and staggering while walking intensified. The level of reactive anxiety (p < 0.01) and personal anxiety (p < 0.001) was reduced significantly in accordance with Spielberger test. Depressive symptoms regressed among 40 % of patients from the basic group against 12 % of patients from the control group. After conducting BFB trainings among patients with CCI the reliable reduce of latent period of cognitive evoked potential P300 in accordance with Fridman (p) was observed: F3 = 0.003; F4 = 0.015; Fz = 0.039; C3 = 0.008; C4 = 0.016; Cz = 0.011; P3 = 0.010; P4 = 0.017; Pz = 0.007 and the significant increase of alpha-activity in the right frontal and parietooccipital, temporal areas was determined. Conclusions.Bioadaptive control is an efficient method of complex treatment for anxiety-depressive disorder, correction of cognitive impairments and changes of neurophysiologic rates among patients with CCI.
Bioadaptive control in complex treatment of psycho-emotional impairments among patients with chronical cerebral ischemia
Keywords: хронічна ішемія мозку; біоадаптивне управління; психоемоційний стан; когнітивні розлади; chronical cerebral ischemia; bioadaptive control; psycho-emotional sate; cognitive impairments